Situation in Spain. Bilbao : memorandum of interview with Jose I. de Lizaso and two other Basque representatives - Citrine, Walter, 1887-1983
1937-04-26 016a-0042-002 MEMORANDUM OF INTERVIEW. Monday, 26th April, 1937. SUBJECT. SITUATlON IN SPAIN. BILBAO. time 5.45. to Reference WMC/FP/335 Present SIR WALTER CITRINE Senor J.I.de Lizaso, ana two other Basque representatives. Tills afternoon I received an unexpected visit from the above representatives of the Basque Government. They told me that they had come specially to thank me for the services I had rendered last week in connection with the attempted blockade by Franco of Bilbao. They said that my action had undoubtedly improved the position, and the food situation, which was critical, had now become considerably eased. They wanted to convey most sincerely the thanks of their government to me. I recounted what had taken place at the interview with Mr. Attlee, Mr. Alexander and Mr. Grenfell at the house of Commons, and explained the difficult position in which the Party had found itself. I also gave an account of the interview. I had had with Mr. Eden, ana subsequently with Sir Robert Vansittart, impressing upon them that the details of the interviews must be treated as confidential. They said they fully understood that, and that they were greatly encouraged by what had transpired. They then went on to say that there was a good deal of interference taxing place with the vessels of the Valencia Government in the Mediterranean. German and Italian warship; were stopping Spanish coasting vessels and searching them. They had no right to do this under the Non-intervention Agreement, as Spain was not a party to that agreement, una the right of search in any case was not conferred upon controlling warships. I asked for details of specific instances, ana this was promised. There was a second point also, namely, that German planes had come over in large numbers into Spain, and only recently some 90 airplanes had been concentrated In an attack upon Bilbao. As far as the Basque representatives could judge, these airplanes were flown over from Germany, via Switzerland and Italy. I pointed out that the distance was a very considerable one, and I doubted whether the range of the planes would allow this to be done. They said, however, that the airplanes were not loaded, ana that they could manage the range comfortably. I then said that while I had heard of isolated cases of planes being flown over Swiss territory 292/946/16a/44(ii)